In a world from which you cannot escape. Parameters of Reality in early proses by Václav Kahuda - Vaníček, Jakub (Bohemica Olomucensia, 2018)
Václav Kahuda's proses have been published continuously since 1992 when the author debuted with the short story called Příběh o baziliškovi. This study is dedicated to the first three Kahuda's proses, Příběh, Veselá bída, and Exhumace. The author's focus is on the possibilities of depiction of the world and one of the basic tendencies for these works: the principle of pleasure, its development and satisfaction. This figuration in Kahuda's works leads to the emergence of a world in which it is not possible to live with dignity, and whose boundaries must be overcome by various ways. In addition to the thematic analysis, which shows how deeply this principle is embedded in the construction of Kahuda's works, the author of the study also focuses on the language means through which Kahuda tries to invent a specific jargon of pleasure. It shows to which extent this language is a practice that violates established cultural standards.
Keywords: contemporary czech literature; possible world; mimesis; modal realism; subversion